Dispersion of surface plasmon-polaritons in weakly periodic structures; Proceedings of SPIE; Vol. 10035 : Atmospheric and Ocean Optics: Atmospheric Physics - Panamarev N. S. Nikolay Semenovich; Donchenko V. A. Valery Alekseevich; Zemlyanov A. A. Aleksey Anatoljevich; Panamareva A. N. Anna Nikolaevna; Shatokhina A. O. Anastasia Olegovna (Optical Radiation Propagation in the Atmosphere and Ocean, 2016)
Title screen